A study of motion about table tennis "step" and "cross step" - Sun, Y.; Sun, M.-L.; Wang, M.-Y. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
In order to make efficient shots, table tennis sport needs to apply flexible and agile step movement. It shows the importance of the step under the requirements of short-range and high speed especially using the techniques of "step" and "cross-step" during a game. Therefore, the purpose of this study is to explore the comparison between the side drive and rush attack with "right-side step" and forehand strokes with "cross step". The research method is using push - side flapping test for the six college table tennis athletes. Six college student athletes are testing their speed of step movement and scoring rate for this study by using "step" and "cross step" techniques for each group and each group is continuously testing for ten sets which each set has three balls. The results showed that there were no significant differences in the speed of movement and the scoring rate between the "step" and "cross step". It`s suggested that the coach apply the training of step and need to find out athletes` personal and reasonable step movement for "step" or "cross-step" training, so that the athletes` steps can have better coordination efficiency.